If You Choose Not to Decide: A Survey of Online Field Experiences for Canadian Teacher Preparation Programs - Siko, Jason P.; Barbour, Michael K.; Archibald, Douglas; Ostashewski, Nathaniel (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2024)
Despite the rapid growth in online and distance learning in Canada, there does not appear to be much interest on the part of teacher education programs to evolve to meet the needs of future generations of teacher candidates. While understanding the notion that systemic change in tertiary education takes time, the steady growth of online and blended learning in Canada–and globally–combined with raised awareness of distance learning stoked by the COVID-19 pandemic should make educators and policymakers worry about failing to respond to a rapidly changing educational landscape. This paper highlights the status of distance and online field experiences provided by Canadian teacher education programs. In addition, we review program offerings to support in-service teachers, such as graduate certificate, degree, and diploma programs, as well as MOOCs offering free professional development. This study, a replication of a mixed-method study originally conducted in the United States and published as a technical report by Archibald et al. (2020), found that a minority of teacher education programs offered online or blended field experiences. Further, we found that programs were slow to change these deficiencies due to institutional lack of resources, limited knowledge base, perceived lack of usefulness for their teachers’ future careers, and regulatory bodies discouraging online field experiences. This study highlights the dramatic need for programming in distance and online education.